2007
DOI: 10.1029/2006ja012115
|View full text |Cite
|
Sign up to set email alerts
|

Remote‐sensing magnetospheric dynamics with riometers: Observation and theory

Abstract: [1] The importance of monitoring particle injection into the inner magnetosphere from the plasma sheet is exceeded perhaps only by its difficulty. The recent progress in using ground-based riometer data [e.g., Spanswick et al., 2007] to detect by proxy particle injection has raised much hope that this important aspect of substorms can be more consistently monitored. In this paper we develop a theoretical model for explaining the observed dispersionless injection events reported by Spanswick et al. The substorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“… Baker et al [1981] found that riometer absorption can be used as an excellent proxy of substorm high‐energy injection at geosynchronous orbit. A series of recent works have further established the viability of using ground‐based riometer arrays to monitor electron injection [ Spanswick et al , 2005, 2007; Liu et al , 2007]. In particular, Liu et al [2007] (hereinafter referred to as LW07) developed a model of electron injection that predicts the riometer response to magnetospheric dipolarization.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… Baker et al [1981] found that riometer absorption can be used as an excellent proxy of substorm high‐energy injection at geosynchronous orbit. A series of recent works have further established the viability of using ground‐based riometer arrays to monitor electron injection [ Spanswick et al , 2005, 2007; Liu et al , 2007]. In particular, Liu et al [2007] (hereinafter referred to as LW07) developed a model of electron injection that predicts the riometer response to magnetospheric dipolarization.…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent works have further established the viability of using ground‐based riometer arrays to monitor electron injection [ Spanswick et al , 2005, 2007; Liu et al , 2007]. In particular, Liu et al [2007] (hereinafter referred to as LW07) developed a model of electron injection that predicts the riometer response to magnetospheric dipolarization. These authors demonstrated that strong electron precipitation is expected to be a by‐product of substorm dipolarization and further investigated in detail how the riometer signal changes during the substorm EP and how the signal intensification is controlled by the magnitude of pitch angle diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a number of events, they found that a sharp rise in plasma sheet electron flux for energies >30 keV (dispersionless injection) was often accompanied (under certain conditions) by a sharp rise in riometer absorption due to sudden enhancement of ionization in the lower ionosphere. If multiple riometers pick up this ionospheric signature of high energy particle precipitation, then tracking the movement of these signatures can give insight into the spatial and temporal evolution of the substorm injection region [Berkey et al, 1974;Liang et al, 2007;Liu et al, 2007;Spanswick et al, 2009]. In this study, we extend this ground-based method of identifying substorm precipitation signatures to GPS TEC, assuming that enhanced electron density due to high-energy particle precipitation will produce detectable TEC enhancements.…”
Section: Introductionmentioning
confidence: 99%